Exploring the Lived Experiences of Senior High School Subanen Students: An Ethnographical Study on Language Learning and Cultural Identity - Ayunan, Dan Michael (International Journal of Sustainability and Advanced Integrated Research, 2026)
This ethnographic-phenomenological study explored the lived experiences of Subanen Indigenous Peoples (IPs) Senior High School students as they navigated English language acquisition within mainstream education while sustaining their cultural identity. Specifically, the study aimed to: (1) describe the experiences of Subanen students in learning English; (2) identify the themes that emerged as they balanced language acquisition and cultural preservation; and (3) develop contextually relevant educational outputs grounded in the findings. 11 Subanen students participated in in-depth interviews. Qualitative data were analyzed using Colaizzi’s phenomenological method to capture the essence of their linguistic and cultural experiences Findings revealed that co-participants viewed English as a vital instrument for communication, academic advancement, and expanded life opportunities. Learning English enhanced classroom engagement, comprehension, and the ability to articulate ideas effectively. However, students also encountered significant challenges, including limited vocabulary, low communicative confidence, and difficulty understanding complex linguistic structures. To address these barriers, co-participants employed multilingual strategies, particularly code-switching among English, Bisaya, and Subanen, demonstrating linguistic adaptability and resilience. Despite increased exposure to English, co-participants maintained a strong commitment to preserving their indigenous identity, language, traditions, and cultural values. Nonetheless, tensions involving identity negotiation, cultural dilution, and language displacement emerged as English assumed a dominant role in formal educational spaces. Based on these findings, two culturally responsive educational outputs were developed: an English Language Instructional Guide and a Cultural Identity Development Framework. These interventions promote a balanced educational approach where English language acquisition and cultural sustainability coexist. The study concludes that English learning among Subanen students is not merely an academic endeavor, but a complex process of identity formation, cultural negotiation, and global readiness anchored in indigenous heritage.